POSSIBILITIES OF CREATIVE THINKING AND ITS MANIFESTATION IN THE EDUCATIONAL PROCESS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article deals with the issues of involving creative, talented youth in creative activities, technologies for the formation and development of social and personal competencies, methodological foundations for the systemic organization of innovative approaches, the importance of increasing the efficiency of developing student creativity.